2016
DOI: 10.18388/abp.2015_1088
|View full text |Cite
|
Sign up to set email alerts
|

Conflicting results of non-invasive methods for detection of Helicobacter pylori infection in children with celiac disease - a preliminary study.

Abstract: CD may increase the risk of divergent results of non-invasive tests used for the detection of HP infection in children. Since UBT is the most reliable test, we suggest its standard use as a method of choice in pediatric CD - at least until new evidence emerges supporting a different approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
0
7
1
Order By: Relevance
“…However, further studies to prove this hypothesis are requested due to some limitations of this study. Jozefczuk et al . suggested that celiac disease may increase the risk of divergent results of noninvasive tests for H. pylori in children due to altered gut motility, superficial gastritis, and/or loose stools, however this has not been proven.…”
Section: Diagnosismentioning
confidence: 99%
“…However, further studies to prove this hypothesis are requested due to some limitations of this study. Jozefczuk et al . suggested that celiac disease may increase the risk of divergent results of noninvasive tests for H. pylori in children due to altered gut motility, superficial gastritis, and/or loose stools, however this has not been proven.…”
Section: Diagnosismentioning
confidence: 99%
“…Therefore, the full-texts of 92 remained articles were completely evaluated. Finally, 26 studies were included in the systematic review and also meta-analysis (kappa (κ) = 0.84) [11,[13][14][15][16][17][18]21,[24][25][26][27][39][40][41][42][43][44][45][46][47][48][49][50][51][52], and the others were excluded due to a reason mentioned in Fig 1 (Fig 1). In the end, there was no suitable cohort study in the included studies.…”
Section: Search Resultsmentioning
confidence: 99%
“…Most studies PLOS ONE were from Turkey (N = 6) [15][16][17][18]51,52] and Italy (N = 5) [11,27,44,45,48]. Some studies had been performed only on children [13,[15][16][17]21,44,47,51,52] or adults [18,25,27,39,43,45,48], the others evaluated both age groups [11,14,42,49,50]. Table 1 shows the details of the included articles.…”
Section: Characteristics Of the Included Articlesmentioning
confidence: 99%
“…BMI was recalculated for patients younger than 18 years according to International Obesity Task Force values (BMI-IOTF corrected) [12]. The presence of HP was assessed using the 13 C isotope-labelled UBT. The 13 CO 2 / 12 CO 2 ratio measurement was carried out using a 13 C-infrared isotope analyser system (IRIS, Wagner Analysen Technik, Bremen, Germany) as described earlier [13,14].…”
Section: Methodsmentioning
confidence: 99%